PENERAPAN MANAJEMEN ZAKAT DALAM MENINGKATKAN PENGUMPULAN ZIS PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN GOWA - Muthmainnah Sultan; Nurfiah Anwar; Trisno Wardy Putra (Fakultas Ekonomi Bisnis Islam, 2023)
The research conducted at BAZNAS Gowa Regency aims to find out how the implementation of the implementation of zakat management in increasing ZIS collection at the National Zakat Agency (BAZNAS) Gowa Regency, the inhibiting and supporting factors for ZIS collection at BAZNAS Gowa Regency and the results of implementing zakat management in increasing fund collection ZIS at BAZNAS Gowa Regency. The type of research used in this study is qualitative using a management approach. Then in research using secondary data and primary data with data collection techniques through observation, interviews, and documentation. The data analysis techniques used are reduction, data presentation, and conclusions/verification. From the results of research that has been carried out at BAZNAS Kab. Gowa. The research results obtained are first, the application of zakat management carried out by BAZNAS in Gowa Regency which consists of Planning, Organizing, Implementation, and Supervision. Second, the inhibiting factors experienced include low public trust in BAZNAS Gowa, human resources managing zakat are less active and creative in using technology, and there is no official BAZNAS office in Gowa Regency. Then the supporting factor in collecting zakat funds at BAZNAS Gowa is UPZ , issuance of a district head circular letter, and cooperation with the ministry of religion. Third, the results of implementing zakat management at BAZNAS Gowa in increasing ZIS collection can be said to be not optimal. This is because there are still some deficiencies in the management of zakat at BAZNAS Gowa